Malay Cuisine Set in Bertam Golf Resort (BGR) / Rashid Salleh … [et al.] - Salleh, Rashid; Abdul Rahim Siddiqe, Ashraf Siddik Khan; Faat, Farhan; Hamir, Norhamizan (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
Pursuing Malay cuisine in Penang is not as easy as you imagine. A lot of food recommendations from foodies in social media were focused on Mamak or Chinese cuisine. As a person from outside Penang and born eating a Malay cuisine, it's a journey for us to search for a restaurant that offers what we want. Our search has found an unexpected place that serves delicious Malay food at a reasonable price. Who would have expected that food at the golf course would serve a set of delicious Malay food at a reasonable price. Bertam Golf Resort is strategically located, making it easy to access from various parts of the region. The resort is located just beside the exit Bertam of PLUS highway. The entrance to the resort is spacious with the beautiful scenery of the golf course. Its setting provides a serene view of the lush golf course, adding to the overall dining experience. The restaurant offers a range of Malay dishes, each crafted to deliver an authentic taste experience.